The suppression of delayed-type hypersensitivity by CD8(+) regulatory T cells requires interferon-γ - Cone, Robert E (Blackwell Publishing Inc, 2007)
CD8(+) regulatory (suppressor) T cells are induced by complex cellular pathways in the spleens of mice that have received an injection of antigen into the anterior chamber (AC) of an eye, an immune-privileged site. Although these CD8(+) regulatory T cells perform an antigen-specific regulatory function for an immune response to self and non-self antigens, the mechanisms of the activation or function of these regulatory cells are not clear. Here, we describe a novel mechanism for the activation of splenic CD8(+) regulatory T cells induced by injection of antigen into the AC. Immunization of mice with trinitrophenyl and bovine serum albumin (TNP-BSA) amplified AC-induced splenic CD8(+) regulatory T cells that suppressed the initiation of contact sensitivity when transferred to immunized, challenged mice. These CD8(+) regulatory T cells were produced independently of perforin, indicating that they are not canonical cytotoxic T cells. Fas ligand (FasL)-deficient CD8(+) regulatory T-cell function was rescued by inclusion of exogenous interferon-γ (IFN-γ), demonstrating that the expression of FasL by CD8(+) regulatory T cells was dispensable, but IFN-γ was not. Ultimately, we demonstrated that the generation of these CD8(+) regulatory T cells occurred independently of IFN-γ, but their suppressor function required IFN-γ receptor stimulation.